A cross-cultural investigation of foster’s image of limited good - Hammer III, Henry B. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
A questionnaire was constructed which was designed to test Foster’s concept of the Image of Limited Good. Students in two sixth grade classrooms in each of two cultures, Mexican and American, were given the questionnaire. The Mexican sample scored higher than the American sample (.01), supporting Foster's concept. A measure of willingness to admit nonconformity was also obtained. The main effect of culture membership upon the measure did not attain significance.